2016
DOI: 10.3855/jidc.7544
|View full text |Cite
|
Sign up to set email alerts
|

Early detection and control of an Acinetobacter baumannii multi-resistant outbreak in a hospital in Quito, Ecuador

Abstract: Introduction: Acinetobacter baumannii (ABA) is an important opportunistic pathogen associated with high mortality rates in intensive care units (ICUs). An outbreak in the ICU of a secondary-level hospital in Quito, Ecuador, occurred during April and May 2015 and was successfully controlled. Methodology: Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) and repetitive element palindromic (REP)-PCR was conducted on all isolates recovered from patients, as well as environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In previous studies, this organism has primarily been investigated in hospitals and the clinical environment. The results of these studies have consistently indicated that A. baumannii is widespread in nosocomial environments [4,17,43]. This organism also prefers to grow in humid conditions.…”
Section: Presence Of a Baumannii In The Aquatic Environmentmentioning
confidence: 79%
“…In previous studies, this organism has primarily been investigated in hospitals and the clinical environment. The results of these studies have consistently indicated that A. baumannii is widespread in nosocomial environments [4,17,43]. This organism also prefers to grow in humid conditions.…”
Section: Presence Of a Baumannii In The Aquatic Environmentmentioning
confidence: 79%
“…29 During nosocomial outbreaks, the colonization in the hospital environment was very important for the transmission of MDRAB, and environmental cultures revealed that numerous sites in ICUs were contaminated with MDRAB. 44 These reports suggested that the high incidence of MDRAB, XDRAB, and NIAB-ICU should be solved immediately, and the medical specialty must undertake most duties. 45 Early recognition and timely implementation of appropriate ICP were crucial in preventing outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, several cases of Acinetobacter baumannii have been reported. The situation with Acinetobacter baumannii CRAB/XCRAB is especially worrying in developing countries like Ecuador, where hospital conditions and policies are not updated, increasing the nosocomial infection risk [ 18 ]. Here, we describe the healthcare-associated infections caused by Acinetobacter baumannii that were identified in different units at the Hospital Teodoro Maldonado Carbo (HTMC), Guayaquil, Ecuador.…”
Section: Introductionmentioning
confidence: 99%